Dynamiques (inter)médiatiques et Technologies Numériques de l’Information et de la Communication dans les démocraties africaines - Idé Hamani; Séverine Equoy Hutin (Communication)
The authors investigate practices related to the appropriation of mobile phones and social networks in Niger and investigate the sociopolitical issues they raise. The study is based on field observations and analysis of Facebook posts gathered during the 2016 presidential election. The authors hypothesize that the recent adoption of these technologies creates unprecedented visibility for the mobilization of Nigerien citizens and a new media dynamic in support of social change in developing countries.